2009
DOI: 10.1097/mph.0b013e3181b258a9
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Atypical Teratoid Rhabdoid Tumor of the Central Nervous System

Abstract: Despite dismal OS, multimodal therapy can induce remission even in metastatic CNS ATRT with partial resection. IT chemotherapy results in higher OS and, because of an overall high rate of distant relapse, should be considered in future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
126
2
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 174 publications
(153 citation statements)
references
References 60 publications
12
126
2
13
Order By: Relevance
“…Since then, additional retrospective studies have demonstrated longer survival in patients with ATRT who received RT. 13,14 Any impact these studies may have had on the use of RT would not be reflected in our results.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Since then, additional retrospective studies have demonstrated longer survival in patients with ATRT who received RT. 13,14 Any impact these studies may have had on the use of RT would not be reflected in our results.…”
Section: Discussionmentioning
confidence: 90%
“…5,11,14 Children aged <3 years constitute the majority of patients who are diagnosed with ATRT. RT in these patients historically has been delayed given the vulnerability to adverse neurocognitive effects on the developing brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations